Efficacy and safety of anlotinib in combination with ¹³¹I therapy in the treatment of distant metastatic differentiated thyroid cancer: a single-arm, phase II study - Li, Yan; Liu, Jianjing; Su, Qian; Liu, Xueyao; Yang, Zhen; Yang, Zhao; Fu, Jie; Zhang, Yan; Tong, Lina; Yang, Fang; Dai, Dong (Frontiers in Oncology, 2025)
BackgroundRadioactive iodine (RAI) is the standard treatment for distant metastatic differentiated thyroid cancer (dmDTC). However, many patients fail to achieve satisfactory effects and prognosis. Anlotinib is a highly effective antiangiogenic tyrosine kinase inhibitor (TKI) that has shown promising efficacy in RAIR-DTC patients. This study evaluated the efficacy and safety of anlotinib in combination with 131I in dmDTC.MethodsThis single-arm, phase II study was prospectively registered on the Chinese Clinical Trial Registry (ChiCTR2500095313). The key eligible criteria included patients with dmDTC who had at least one measurable metastatic lesion capable of iodine uptake and were planned to receive RAI therapy. Previous treatment with TKI was not permitted. Patients underwent a whole-body iodine scan (Rx-WBS) following iodine administration on days 3-5. When confirmed iodine uptake in metastatic lesions, anlotinib would be given at 12 mg (QD, 2 weeks on/1 week off, Q3W) initially. One combination treatment cycle consisted of 12 weeks of anlotinib and 1 dose of iodine-131. The primary endpoints were the objective response rate (ORR) and changes in thyroglobulin (Tg) levels. The secondary endpoints included disease control rate (DCR), progression-free survival (PFS), and safety.ResultsFrom October 2022 to September 2024, 20 patients (4 males and 16 females) with distant metastatic DTC were enrolled. All patients who had completed at least one cycle of combined treatment were eligible for data analysis. The median follow-up was 13.7 months. 11 patients achieved partial response (PR), 8 patients achieved stable disease (SD), and 1 patient had progressive disease (PD). ORR and DCR were 55.0% [95% Confidence Interval (CI): 31.5%-76.9%] and 94.7% (95% CI: 75.1%-99.9%) respectively. Median PFS was not reached. All patients achieved a biochemical response according to protocol-defined criteria, defined as a ≥25% decrease in Tg levels. Grade 3 or higher treatment-related adverse events (TRAEs) were observed in 10 (50%; most common hypertension) patients. Dose reductions of anlotinib were required in 10 (50%) patients due to AEs, and no patient discontinued treatment because of AEs. No serious adverse events (SAEs) or deaths were reported.ConclusionsThis study demonstrates the promising efficacy and safety of combining the TKI with 131I therapy, suggesting that anlotinib may be a viable option for dmDTC.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=226033, identifier ChiCTR2500095313.